Legal Pluralism and Inheritance Rights: Resolving Conflicts Between Local Customs and National Law in Indonesia - Syahrial Haq, Hilman (Universitas Muhammadiyah Purwokerto, 2025)
This study describes efforts to resolve the conflicts of local and national law on the customary inheritance practice of the Sasak community. This research was conducted in several areas on the island of Lombok, namely Sade Hamlet, Teruwai Village, Penujak Village, and Bayan Village by using data collection methods in the form of library studies, interviews, and observations to then be analyzed qualitatively through a case approach, legislation, and history. The result obtained that the local law conflict and the national law in the practice of the Sasak community customary inheritence motivated by the difference woman's position in the strata customary inheritence based on the jurisprudence remains the supreme court number 179K/SIP/1974 and number 1589K/SIP/1974 with the concept of Sasak community inheritance which has patrillineal characteristic. Permanent jurisprudence requires that the daughter and son of an heir are jointly entitled to the inheritance in the sense that the son's share is the same as the daughter's, while the traditional inheritance of the Sasak community places sons as heirs to their parents' throne (anaq prangge) so that property in the form of houses, gardens, rice fields and livestock will be passed down to the sons, while the daughters only receive property stored in the house, such as jewelry and beads as provisions for her marriage life. This reality might be caused some latent and manifest conflict which can be ended in the court. Therefore, a continuous dialogue is needed by reviving the community mediation such as krame dese or bale sangkep as a means of finding an ideal final format which is acceptable to all parties so that legal convergence occurs between the two legal systems in the traditional inheritance practices of the Sasak community.